Hidden levees: Small-scale flood defense on rural coasts. (December 2022) - Hall, Emily A.; Molino, Grace D.; Messerschmidt, Tyler C.; Kirwan, Matthew L.
Abstract: Climate change, land subsidence, and coastal population growth are increasing coastal flood risks and changing land uses. Large-scale levee systems protect many urban areas from flooding, but much less is known about how rural coasts respond to sea level rise and increasing flood risks. This study examined previously unreported, small-scale earthen levees that have been constructed for centuries by individual landowners in rural, low-lying portions of the Chesapeake Bay region in the USA. Analysis of aerial imagery, digital elevation models, and field measurements revealed that levees are constructed from inorganic silt loam sediment consistent with adjacent terrestrial soils. They extend above Highest Astronomical Tide, and are today surrounded by marsh or low-lying terrestrial vegetation. Although preliminary measurements revealed inconsistent effects of levees on soil salinity or soil organic content, the landward side of levees are generally lower in elevation than the seaward side. They are also characterized by less flood tolerant vegetation and shallower organic-rich soils. These results suggest that small-scale levees may have historically impeded wetland development, though their effects today are unclear. This work highlights a historical approach to rural flood defense and suggests that, in some cases, the impacts of small levees are observable long after coastal retreat and levee abandonment. They are therefore part of the evolving human-landscape system for potential management into the future.